Electrical characterization of polymer nanocarbon composites and high yield exfoliation of graphene - Hernández, Yenny R. (Trinity College (Dublin, Ireland). School of Physics, 2009)
The high aspect ratio, outstanding mechanical properties and high conductivity of carbon nanotubes makes them ideal candidates for polymer reinforced conducting composites. Solution processed composites, based on polyvinylalcohol and multiwalled nanotubes, have been fabricated for a range of volume-fractions using three solvents; water, 1-methyl-2-pyrrolidinone (NMP) and dimethyl sulfoxide (DMSO). Electrical tests were carried out on each composite, demonstrating that the electrical properties depend strongly on the solvent used.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.